ANALISIS KETERLAMBATAN PEMBERITAHUAN PENGAMBILALIHAN SAHAM DITINJAU DARI HUKUM PERSAINGAN USAHA TIDAK SEHAT (STUDI KASUS PUTUSAN NO.17/KPPU-M/2020) - Salsabilla Hassani, (2022)
Based on article 29 of Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, it is explained that the takeover of shares that have asset values and or sales values exceeding a certain amount as regulated in Article 5 of Government Regulation No. 57 of 2010 must carry out notification to KPPU no later than 30 working days after it is legally effective. However, it was found that through the KPPU's decision No.17/KPPU-M/2020 it was stated that PT. Saratoga Investama Sedaya was proven to have violated Article 29 of Law No. 5 of 1999 in conjunction with Article 5 of PP No. 57 of 2010. This study aims to find out how to prove the element of violation of the delay in notification of the takeover of shares by PT. Saratoga Investama Sedaya and to understand the role of KPPU in supervising business competition in order to ensure legal certainty and prevent monopolistic actions and unfair business competition. The preparation of this thesis uses a normative juridical method by reviewing library data such as laws and regulations, books and internet sources. The conclusion in this study is that the Commission Council stated that the takeover of shares by the Reported Party did not in fact have the potential to cause monopolistic practices and/or unfair business competition. Due to the absence of changes in market forces and the absence of vertical integration. However, the Reported Party must bear a fine of Rp. 1 billion because it was declared to have violated Article 29 of Law No. 5 of 1999 in conjunction with Article 5 of PP No. 57 of 2010. One of the efforts of the government and KPPU in realizing a world of fair business competition and avoiding monopolistic practices, is by increasing socialization from the public. KPPU so that the public understands the duties, authorities, roles, and functions of KPPU in contributing to economic activities in Indonesia.